Climate change and biodiversity - Lovejoy, Thomas E.; Hannah, Lee Jay. (New Haven, Conn. Yale University Press, 2005)
"In the past, climate changes have had dramatic repercussions, including large numbers of extinctions and extensive shifts in species ranges. As human-induced climate change accelerates, scientists and policymakers involved with biodiversity conservation need authoritative information in order to design effective plans and responses. Climate Change and Biodiversity meets this need. Written for the specialist as well as the concerned citizen, this important book presents a comprehensive view of the newest research and thinking on climate change and biological diversity."--Book Jacket.
Biodiversity and climate change in context / Lee Hannah, Thomas E. Lovejoy and Stephen H. Schneider -- What is climate change? / Thomas R. Karl and Kevin E. Trenberth -- Recent climate trends / Mike Hulme -- Biotic response: range and abundance changes / Camille Parmesan -- Case study: detection at multiple levels: Euphydryas editha and climate change / Camille Parmesan -- Present and future phenological changes in wild plants and animals / Terry L. Root and Lesley Hughes -- Case study: responses of natural communities to climate change in a highland tropical forest / J. Alan Pounds, Michael P.L. Fogden and Karen L. Masters -- Recent evolutionary effects of climate change / Chris D. Thomas -- A "paleoperspective" on climate variability and change / Jonathan Overpeck, Julia Cole and Patrick Bartlein -- North temperate responses / Brian Huntley -- Tropical biotic responses to climate change / Mark B. Bush and Henry Hooghiemstra -- Case study: a record of change from the high plain of Bogota / Mark B. Bush -- Southern temperate ecosystem responses / Vera Markgraf and Matt McGlone -- Case study: microrefugia and macroecology / Matt McGlone and Jim Clark -- Responses of marine species and ecosystems to past climate change / Kaustuv Roy and John M. Pandolfi -- Genetic and evolutionary impacts of climate change / Godfrey M. Hewitt and Richard A. Nichols -- Case study: phylogeny and distribution of fishes of the Characidium lauroi group as indicators of climate change in southeastern Brazil / Paulo A. Buckup and Marcelo R.S. Melo -- Climate change projections and models / Sarah C.B. Raper and Filippo Giorgi -- Modeling distributional shifts of individual species and biomes / A. Townsend Peterson ... [et al.] -- Case study: Modeling species range shifts in two biodiversity hotspots / Guy F. Midgley and Dinah Millar -- Dynamic ecosystem and earth system models / Richard A. Betts and Herman H. Shugart -- Case study: migration of vegetation types in a greenhouse world / Jay R. Malcolm ... [et al.] -- Climate change and marine ecosystems / Ove Hoegh-Guldberg -- Climate change and freshwater ecosystems / J. David Allan, Margaret Palmer and N. Leroy Poff -- Case study: Climate change impacts on soil biodiversity in a grassland ecosystem / Diana H. Wall -- Synergistic effects / Bert G. Drake ... [et al.] -- Case study: avian malaria, climate change, and native birds of Hawaii / Dennis LaPointe, Tracy L. Benning and Carter Atkinson -- Conservation with a changing climate / Thomas E. Lovejoy -- Designing landscapes and seascapes for change / Lee Hannah and Lara Hansen -- Case study: integrating climate change into Canada's National Park System / Daniel Scott -- Managing the matrix / Gustavo A.B. da Fonseca, Wes Sechrest and Judy Oglethorpe -- Case study: Managing for future change on the Albemarle Sound / Sam H. Pearsall, III -- Protected areas management in a changing climate / Lee Hannah and Rod Salm -- Emissions reductions and alternative futures / Robert T. Watson -- Global greenhouse gas levels and the future of biodiversity / Thomas E. Lovejoy and Lee Hannah.
Includes bibliographical references and index.
Keywords: Biodiversity -- Climatic factors